2015
DOI: 10.12816/0016622
|View full text |Cite
|
Sign up to set email alerts
|

Some Phenotypic Characteristics of Wool and Hair of Both Goat and Camel

Abstract: Antalya İ linde K ı l Keçisi Yeti ştiricili ğ inin Baz ı Yap ısal Özellikleri Il. Bazı Üreme Özellikleri, Sa ğı m ve K ı rk ı m Dönemi Uygulamaları Gürsel DELLAL1 G e l i ş Tarihi : 07.09.2000 Özet: Bu araşt ı rmada, Antalya ilinde Merkez, Korkuteli, Elmal ı , Kaş, Manavgat, Gündo ğ muş ve Gazipaşa ilçelerinde Kıl Keçisi yeti ştiricili ğine yer veren tarı m işletmelerinin baz ı üreme özellikleri , sa ğı m ve kırk ı m dönemi uygulamalar ı ve yetiştiricilikte kar şı laşı lan sorunlar gibi yap ısal unsurlara ili … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In our study, the one-humped camel hair medulla had a variety of patterns and structures, including a continuous pattern and an amorphous structure (75%, 70%, and 90% in the G1, G2, and G3 groups, respectively), as well as interrupted intruding amorphous, interrupted, vacuolated, or amorphous medulla and fragmented amorphous medulla (25%, 30%, and 10% in the G1, G2, and G3 groups, respectively). Previous research has shown that the medulla of Maghrebi camel hair fibers was 50% continuous, 38% fragmented, and 12% interrupted [ 45 ]. The adult male one-humped camel’s cortex was pigmented, and the medulla had a continuous, smooth margin [ 13 ] and camel hair is divided into two parts: thin, non-medullated, or medullated hair fibers and thick, interrupted, or continuous medulla hair fibers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the one-humped camel hair medulla had a variety of patterns and structures, including a continuous pattern and an amorphous structure (75%, 70%, and 90% in the G1, G2, and G3 groups, respectively), as well as interrupted intruding amorphous, interrupted, vacuolated, or amorphous medulla and fragmented amorphous medulla (25%, 30%, and 10% in the G1, G2, and G3 groups, respectively). Previous research has shown that the medulla of Maghrebi camel hair fibers was 50% continuous, 38% fragmented, and 12% interrupted [ 45 ]. The adult male one-humped camel’s cortex was pigmented, and the medulla had a continuous, smooth margin [ 13 ] and camel hair is divided into two parts: thin, non-medullated, or medullated hair fibers and thick, interrupted, or continuous medulla hair fibers [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The medullary index in camels is also varied; in Bactrian camels, the medullary index was less than 1/4 of the hair diameter (16.63 to 16.86 μm), whereas, in the Llama, the medullary index was about 1/3 of the hair diameter, ranging from 33.33 μm to 33.96 μm [ 50 ]. Camel hair had a medullary index percentage of approximately 78.66% [ 45 ]. The medulla within adult male dromedary camels was found to be more than half the diameter of their hair [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reported concentrations of calcium, magnesium, copper, zinc, iron and manganese were 549.6±74. Helal (2015) who reported higher concentrations of B, Cd, Co, Cr, Fe, Mn, Ni and S in fine hairs of Maghrebi camels while Mo, Pb and Zn were higher in coarse fibers. Furthermore, the similar studies done on horses (Or et al, 2004) and yaks (Chattergee et al, 2005) revealed that level of some mineral elements were affected by nutritional differences.…”
Section: Hair Mineral Analysesmentioning
confidence: 92%
“…Yarn elongation of control wool grade had the highest value followed by soft and medium wool grades, respectively and the lowest value of yarn elongation was that of harsh wool grade. Helal et al (2008) reported that yarn elongation tended to increase with the increase of fineness, which might be related to the increase in fiber crimps. For plied yarn, sorting system significantly (P< 0.05) affected yarn count and significantly (P< 0.01) affected yarn strength, tenacity and twisting (Table 5).…”
Section: Yarn Characteristicsmentioning
confidence: 96%
“…), respectively and the lowest was that of control wool grade (893.90 ±29.5 gf.). Helal et al (2008) reported that yarn tenacity tended to decrease with the increase in fiber diameter and staple length. The increase in yarn strength may be due to the increase of numbers of fibers in the yarn cross section.…”
Section: Yarn Characteristicsmentioning
confidence: 99%